Barrier Adaptive First Order Sliding Mode Differentiator. Issue 1 (July 2017) - Obeid, H.; Fridman, L.; Laghrouche, S.; Harmouche, M.
Abstract: An algorithm for adaptation of first order sliding mode differentiator gains is proposed for the case when the upper bound of the second derivative exists but it is unknown. The proposed barrier adaptive algorithm can ensure the convergence of the differentiator to some vicinity of the first derivative. Then, a convergence detection criteria is used to estimate the size of this vicinity. The properties of the proposed algorithm in the presence of noise are discussed.